DAMPAK KERUSAKAN HUTAN DALAM KARYA LUKIS SUREALIS - Slamet Suono; Yasrul Sami (Serupa The Journal of Art Education, 2021)
This final work aims to visualize the impact of forest destruction in surrealist paintings, the bad effects that occur due to forest destruction are very many, including air pollution, floods, landslides, drought to the threat of animal habitats in the forest. The principle of making this final work uses five stages, namely the preparation stage, the elaboration stage, the synthesis stage, and the concept realization stage, starting with sketching, moving the sketch, equipment and materials, working and finishing procedures. The last stage is refinement to exhibition. Ten of the works raised were visualizing the impact of forest destruction in surrealist paintings.Kata kunci: Dampak kerusakan, surealis.